Tonåringars värderingar och attityder till mat - Wesslén, Annika (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2000)
Teenage is associated with search for independence, identity and changes in lifestyle. Many studies have identified dietary intake and food choice of teenagers, but only a few have discussed why teenagers choose the food and the meals they do. The present study focuses on high school students in the process of forming adult behaviour patterns and describes their ideas related to food and the ways in which food is used in their everyday life. The focus group interview method was used. Eighteen focus groups were held including 136 teenagers (60 males, 76 females, mean age of 17 years) from five senior high schools in two geographic regions Uppsala and Bollnäs. Each group consisted of 6-8 teenagers. Interviews lasted for 90 minutes and followed a questionnaire. All conversations were taped, transcribed word-by-word. Food habits, behaviours and attitudes were mostly influenced by the family, particularly the mother, but not by friends. Proper food was defined as homemade and fast food was eaten for pleasure. Eating should mostly be fast and food simple to prepare, and they were unwilling to give time priority to eating or cooking. Boys regarded meals merely as a way to satisfy their hunger, and cared for portions to be enough for this, but they were less particular of what they ate. Girls found situations that included eating to be important also as social forums and worried about too much food ruining their body appearance, as keeping a slim, healthy look was coupled to success. Taste was most important when making choiced of different foods.